(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Birds are ideal models for studying speciation because of their wide range of traits andaccompanying spatial patterns. For centuries, morphological procedures were the preferred method fordetermining the degree of relatedness between species and intraspecific variation, until moleculargenetic investigations gravely questioned traditional morphology-based results. However, with theadvancement of multivariate statistics and the ease with which morphological, phylogenetic, andecological information can be combined, morphology is being reconsidered as a valuable tool forornithological research. This chapter examines the most essential features of morphological variation inbirds, including how to assess its plasticity and how phenotypic variation can be included into a largerevolutionary framework that explains avian body alterations in light of speciation events.